PENGARUH PERPUTARAN AKTIVA, PIUTANG DAN HUTANG TERHADAP PROFITABILITAS PT. BUKIT ULUWATU VILLA Tbk - Ni Luh Putu Anom Pancawati (Fakultas Ekonomi Universitas Islam Al-Azhar, 2018)
This study aims to test and analyze the effect of asset turnover, receivable turnover and debt turnover to profitability at the company PT. Bukit Uluwatu Villa Tbk from 2009 to 2017. Measurement of profitability in this study using Return On Assets (ROA) . The method used in this research is descriptive statistic with multiple linier regression analysis technique. The results of this study indicate that the independent variables of asset turnover, receivable turnover and debt turnover have no effect simultaneously on the dependent variable of profitability (ROA) and partially each independent variable has no positive effect on the dependent variable of profitability (ROA).